LANGUAGE ATTITUDE OF CINA BENTENG COMMUNITY TANGERANG - Queency; Sonya Ayu Kumala (Bhumantara, 2026)
This research examines the language attitudes of the Cina Benteng community in Tangerang, focusing on how its members perceive, value, and use their heritage language in comparison to dominant languages such as Bahasa Indonesia and English. Grounded in sociolinguistic theory, particularly the concept of language attitude, the study employs a qualitative descriptive method through interviews and questionnaires with respondents from different age groups to capture generational variations in language perception. The analysis, conducted through thematic categorization, highlights aspects such as language preference, cultural expression, language shift, and intergenerational transmission. Findings reveal a complex interplay between pride in cultural heritage and pressures of linguistic assimilation, where older generations show stronger positive attitudes toward preserving the native language, while younger members prefer more dominant languages for reasons related to education, employment, and social mobility. These insights emphasize the urgency of strategic efforts in language preservation, cultural education, and community engagement to sustain the linguistic identity of the Cina Benteng people.